POVERTY MODELING IN WEST KALIMANTAN USING STRUCTURAL EQUATION MODELING - PARTIAL LEAST SQUARE - Perdana, Hendra; Novita, Irene; Fauzan, Muhammad; Nurhanifa, Nurhanifa (VARIANCE: Journal of Statistics and Its Applications, 2024)
Poverty remains a pervasive issue across various regions in Indonesia, often leading to significant repercussions such as hindering economic growth and exacerbating inflationary pressures within localities. Poverty has emerged as a formidable challenge for the global community, particularly for developing nations, including Indonesia. West Kalimantan is a province in Kalimantan Island with high poverty rates. This research examined the factors influencing poverty within West Kalimantan Province in 2022 using the Structural Equation Modeling-Partial Least Square (SEM-PLS) method. This research analyzed the interrelations among poverty, education, economy, and health dimensions. Findings indicated a significant relationship between health and education dimensions. In contrast, the relationships between economic dimensions and poverty, health and the economy, and education and the economy were insignificant.